Hubungan Spiritualitas dan Kualitas Kehidupan Kerja Perawat dengan Kepuasan Kerja Perawat di Ruang Rawat Inap Rumah Sakit Umum Daerah Andi Muhammad Parikesit Tenggarong - Maridi M. Dirdjo (Universitas Muhammadiyah Kalimantan Timur, 2017)
Background: Aspects of spirituality can make a person more able to interpret the meaning of life and have self-acceptance of any condition so as to give a positive response to the changes that occur in him. Having a high spirituality will make a person more creative in determining things that are intrapersonal and interpersonal, and can increase job satisfaction. Moreover, if followed by improving the quality of work life of nurses, so that the opportunity for them to develop using their skills and competence, good relationships, work participation, and a conducive working environment can provide nurse’s work satisfaction so as to increase productivity for the hospital.Research Objectives: This study aims to determine the relationship between the nurse’s spirituality and quality of work life with job satisfaction of nurses at inpatient wards of RSUD AM Parikesit Tenggarong.Research Method: This research design used descriptive correlation with cross sectional approach. The research variables were measured through questionnaires using The Quality of Nursing Work Life Scale (Beth A, 2001) for the quality of nurse’s work life and Index Of Work Satisfaction (Stamp, 1997) for nurse’s job satisfaction, while spirituality used self-developed questionnaires 16 item statement and has been declared valid and reliable. The sampling technique used was proportionate stratified random sampling of 109 people. Data analysis was by using parametric test person product moment.Result: The result of stastitic test got p value of spirituality 0.193 and quality of work life 0.04. Which means there is no significant relationship between the nurse's spirituality with the nurse's job satisfaction but has a positive relationship direction. While there is a significant relationship quality of work life with job satisfaction of nurse, patterned positive.Conclusion: The need for spirituality still needs to be improved because it becomes an important aspect in the nursing process that is not only for the same nurse but also for the client. In addition, the quality of work life of the nurse must be maintained and enhanced again. Hospital management is recommended to facilitate formal and informal learning in teamwork related to understanding spirituality, and improve working conditions in the nursing environment.